Acute ST-Elevation Myocardial Infarction in a 25-Year-Old Female with Polycystic Ovary Syndrome: A Cardiometabolic Risk in Women of Reproductive Age - Kenlie, Elbert Aryo; Wahjoepramono, Nicolaus N.; Sito, William W.; Triaswhoro, Giuseppe L (The Indonesian Heart Association, 2025)
Background Acute myocardial infarction is relatively rare in young patients. The age of onset gradually decreases due to multiple risk factors. The causes of Myocardial Infarction (MI) among patients aged less than 45 can be divided into four groups: atheromatous coronary artery disease, non-atheromatous coronary artery disease, hypercoagulable states, and MI related to substance misuse. Case Illustration A 25-year-old female came to the emergency department with chest discomfort for the past 40 minutes, has a history of diabetes for the past 3 years, and a Polycystic Ovary Syndrome (PCOS) history. Her vital signs show elevated Blood Pressure (BP) 150/100 mmHg. ECG showed sinus rhythm with ST elevation in the anterior leads. Random Blood Glucose (RBG) was 477 mg/dL, High Sensitivity (HS)-troponin 403 ng/L, and blood ketone3.1 mmol/L. She was initially treated with: ticagrelor 180 mg, Acetosal 320 mg, insulin 4 u/hour. She was diagnosed with ST-Segment Elevation Myocardial Infarction (STEMI) and Diabetic Ketoacidosis (DKA). Coronary angiography revealed 95% stenosis in proximalLeft Anterior Descending (LAD) and was treated as the culprit lesion, while 85% stenosis in mid Right Coronary Artery (RCA) was considered as the residual stenosis. Primary Percutaneous Coronary Intervention (PCI) was initiated at the proximal LAD, and post-PCIangiography showed a good result with TIMI 3 flow to the distal LAD. Conclusion PCOS increases cardiovascular risk primarily by promoting insulin resistance and metabolic dysfunction. Young individuals suspected of elevated cardiovascular risk should undergo acomprehensive cardiometabolic evaluation. PCI remains the cornerstone treatment for STEMI across all ages due to its well-established mortality benefit.